Conservative treatment of developmental dysplasia of the hip in Kuwait - Rejholec, M; el-Sisi, H (Sbornik lekarsky, 2001)
This paper evaluates the results of conservative treatment for developmental dysplasia of the hip after an average follow-up of 3 years in 69 patients and 99 hips: 31 bilateral, 23 left side, and 14 right. They were treated at the Al-Razi Hospital, Kuwait, between January 1995 and December 1996. There were 59 girls and 10 boys aged between 5 months and 24 months (average age 12 months). The treatment consisted of traction for 1 or 2 weeks, followed by manipulation in 36 hips and manipulation with adductor longus tenotomy in 45 hips and with adductor longus and psoas tenotomy in 18 hips. Avascular necrosis of the femoral head developed in 16 hips (16%): 14 hips on the affected side and 2 hips on the unaffected side. Persistent acetabular dysplasia was present in 13 hips, subluxation in 9 hips and dislocation in 13 hips. Open reduction was later required in 5 hips, open reduction and innominate osteotomy in 8 hips, and hip extracapsular innominate osteotomy in 1 hip. The results were evaluated according to the age groups with highest rate of complications after the age of 15 months. The treatment protocol was changed to limit conservative treatment until the age of 14 months.
Keywords: Kuvajt; trakce; Kuwait; Traction; Hip Dislocation, Congenital; mužské pohlaví; ženské pohlaví; manipulace ortopedická; Infant; Manipulation, Orthopedic; vývojová kyčelní dysplazie; retrospektivní studie; Humans; Female; Retrospective Studies; kojenec; lidé; Male